The Effect Of Entrepreneurship Education And Digital Literacy On Entrepreneurial Intention Mediated By Entrepreneurial Self-Efficacy In Vocational High School Students In Malang City - Khoiriyah, Siti Nur; Heri Pratikto; Titis Shinta Dhewi (International Journal of Business and Quality Research, 2025)
This study aims to examine the influence of entrepreneurship education and digital literacy on entrepreneurial intention among vocational high school (SMK) students in Malang City, with entrepreneurial self-efficacy as a mediating variable. A quantitative approach was used with hypothesis testing methods. The research sample involved 226 twelfth-grade students from several SMKs in Malang City. Data analysis was performed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) technique. The results showed that entrepreneurship education and digital literacy had a positive and significant effect on entrepreneurial self-efficacy and entrepreneurial intention. In addition, it was found that entrepreneurial self-efficacy acts as a partial mediator in the relationship between digital literacy and entrepreneurial intention, as well as a full mediator in the relationship between entrepreneurship education and entrepreneurial intention. These findings confirm that entrepreneurship education and the improvement of digital literacy play an important role in strengthening the entrepreneurial confidence and entrepreneurial intention of vocational high school students, in order to prepare them to become graduates who are ready to work or create their own jobs